Is preoperative state anxiety a risk factor for postoperative delirium among elderly hip fracture patients?. Issue 8 (14th August 2015) - Van Grootven, Bastiaan; Detroyer, Elke; Devriendt, Els; Sermon, An; Deschodt, Mieke; Flamaing, Johan; Dubois, Christophe; Milisen, Koen
Abstract : Aim: To determine if preoperative state anxiety is a risk factor for postoperative delirium in older hip fracture patients. Methods: A secondary data analysis comprising data from a prospective non‐randomized trial including 86 patients with a hip fracture aged 65 years and older was carried out. State anxiety was measured preoperatively using the State‐Trait Anxiety Inventory. Delirium and its severity was measured pre‐ and postoperatively (day 1, 3, 5, 8) by trained research nurses using the Confusion Assessment Method and Delirium Index. Results: A total of 24 patients (27.9%) developed delirium postoperatively. Preoperative state anxiety (State‐Trait Anxiety Inventory) was not associated with postoperative delirium (rb = 0.135, P = 0.353), duration of postoperative delirium (rho = 0.038, P = 0.861) or severity of postoperative delirium (rho = 0.153, P = 0.160). Independent predictors of postoperative delirium were lower MMSE scores (OR 0.75, 95% CI 0.60–0.95, P = 0.015), osteosynthesis surgery (OR 3.66, 95% CI 1.02–13.15, P = 0, 047) and lowest intraoperative diastolic blood pressure (OR 0.92, 95% CI 0.85–0.99, P = 0.031). Conclusion: No relationship between state anxiety and postoperative delirium was found, but significant methodological hurdles were observed and discussed providing important groundwork for further research in this area. Further research should focus on reliable measurement of state anxiety in cognitively impaired older populations.Geriatr Gerontol Int 2016; 16: 948–955.